Teaching innovation in internal control courses integrating ideological education and game theory - Xie, Danyang; Ou, Kaili (Frontiers in Physics, 2025)
This study aims to propose an innovative teaching model for Internal Control courses, integrating course ideology and game theory perspectives to enhance learning engagement. The developed model—termed “Integration, Co-learning, Co-empathy”—comprises three phases: initial design, mid-term application, and final assessment. Integration constructs a cohesive knowledge structure; Collaborative Learning boosts students’ practical skills; empathy strengthens emotional literacy and fosters a positive teacher-student relationship. By merging ideological and political education concepts with game theory principles, the research optimizes course design and teaching strategies. It offers insights into the continuous development of Internal Control courses in accounting programs, providing practical recommendations for university-level curriculum reform. Ultimately, it targets improved educational effectiveness and promotion of comprehensive learning.